PENGARUH METODE JARIMATIKA TERHADAP KEMAMPUAN NUMERASI PADA MATA PELAJARAN MATEMATIKA DI KELAS III SD NEGERI PAHLAWAN - Al-Muharram, Muhammad Dimas; Endang Yuda Nuryenda; Rokhmatun Nabillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the Jarimatika method on the numeracy skills of third-grade students at SD Negeri Pahlawan. The research employed a quantitative approach using a quasi-experimental design with a nonequivalent pretest–posttest control group design. The sample consisted of 30 students divided into an experimental group and a control group. Data were collected through observation and numeracy skill tests, while data analysis included normality testing, homogeneity testing, the Mann-Whitney test, and mean score analysis. The results showed that the posttest scores of the experimental group increased significantly compared to those of the control group. The Mann-Whitney test produced an Asymp. Sig. (2-tailed) value of < 0.05, indicating a significant difference in numeracy skills between the two groups. The average percentage score of the experimental class reached 62.71% (effective category), which was higher than the control class at 53.63%. Observation results also revealed that the implementation level of the Jarimatika method reached 87%, categorized as very practical. Improvements in numeracy skills were observed across three indicators: the use of numbers in daily contexts, data interpretation, and decision-making based on calculations. Therefore, it can be concluded that the Jarimatika method has a positive and effective impact on improving elementary students’ numeracy skills.